EPR Study of Porous Si:C and SiO2:C Layers. Issue 6 (5th January 2018) - Savchenko, Dariya; Vasin, Andrii; Muto, Shunsuke; Kalabukhova, Ekaterina; Nazarov, Alexei
Abstract : Initial porous silicon (por‐Si), carbonized porous silicon (por‐Si:C), and carbon‐incorporated porous silicon oxide (por‐SiO2 :C) layers are studied by electron paramagnetic resonance (EPR) at T  = 10–13 K. Scanning transmission electron microscopy and electron energy loss (EEL) spectroscopy show that por‐Si:C and por‐SiO2 :C layers have a highly disordered structure with mixing sp 2 and sp 3 CC bonds. In the por‐SiO2 :C layers, the peak of the oxygen bonded to carbon in the form of hydroxyl groups is found in the EEL spectrum of the C K‐edge region. Low‐intensity signals of Lorentzian lineshape are detected in the EPR spectrum of por‐Si, por‐Si:C, por‐SiO2 :C layers. One of them is attributed to the Pb0 defect at the Si/SiO2 interface of nanocrystalline grain and the second to the silicon dangling bonds (SiDB) localized in nanocrystalline Si. The carbonization of por‐Si layers and subsequent oxidation of por‐Si:C gives rise to the appearance of additional EPR signals of high intensity at g  = 2.0035(3) in por‐Si:C and at g  = 2.0030(3) in por‐SiO2 :C, which are assigned to carbon‐related defects (CRD) and carbon clusters, correspondingly. It was found that predominant defect types in por‐Si:C and por‐SiO2 :C layers are CRD and carbon clusters, respectively, while the spin concentration of Pb0 interface defects and SiDB is low. Abstract : Three electron paramagnetic resonance (EPR) signals, due to the Pb0 defect at the Si/SiO2 interface, silicon dangling bonds (SiDB), and carbon‐related defect (CRD), respectively, were observed in carbonized porous silicon (por‐Si:C). The oxidation of por‐Si:C gives rise to the formation of carbon clusters and the decrease of CRD spin concentration thanks to the formation of COH carboxylic groups.